Non-impact Trajectory Planning and Dynamics Simulation Analysis of Four-DOF Manipulator - Liu Lei; Zhu Xinglong; Yin Junyao (Jixie chuandong)
In the research of robotic manipulator，trajectory planning and dynamics analysis are very important.In view of the structural characteristics of the four-DOF manipulator for electro test and installation of ground wire，the dynamics model is established by Lagrange method and the dynamics analysis is carried out.On the basis of fourth order polynomial，the non-impact trajectory planning is proposed.The Simulink module in Matlab is used to get the curve of the moment and force of each joint changing with time.Using Adams software to carry out dynamics simulation，the moment and force curve of each joint are got，and compare with the curve calculated by Simulink，the correctness of dynamic analysis are confirmed，the foundation for the next structural design and system control is laid.